Preparation Of Soap from Palm Kernel Oil (Pko) And Potash - Ibrahim Jimoh; Abdullahi Jimoh (Genius Publishing Group, 2021)
The soap was prepared from Palm Kernel oil with Potassium hydroxide and other additives using cold method. The staining property, solubility property, lather formation and cleaning action of the sample Soap were accessed. The pH-values of the sample Soap were obtained, ranging from 9.06-9.08. The soap prepared with additives mentioned and a pH Value does not irritate the skin and has good lather forming characteristics.
Keywords: Soap; palm kernel; potash